Long-term outcomes of colorectal cancer patients with and without malignant large-bowel obstruction. (25th July 2018) - Munakata, Shinya; Murai, Yuta; Koiuzumi, Akihiro; Kato, Hisaki; Yamamoto, Riku; Ueda, Shuhei; Tokuda, Satoshi; Sakuraba, Shunsuke; Kushida, Tomoyuki; Orita, Hajime; Sakurada, Mutsumi; Maekawa, Hiroshi; et al.
Aim: Colorectal cancer patients with malignant large-bowel obstruction (MLBO) require emergency treatment. Here we evaluated the long-term outcomes of recurrence and prognosis (not short-term mortality or nonocclusive cancer T1–T2) in colorectal cancer patients with and without an MLBO.Methods: We retrospectively analyzed the cases of the consecutive patients who underwent curative resection for colon cancer. We compared the groups regarding patients' age and gender, the tumor location, T and N factor, tumor stage, disease-free survival and overall survival.Results: The nonobstruction group had a significantly longer disease-free survival and overall survival compared with the MLBO group.Conclusion: MLBO was associated with cancer recurrence and poorer overall survival regardless of the staging and adjuvant chemotherapy.